DAMPAK PENGEMBANGAN PARIWISATA DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI KABUPATEN LOMBOK BARAT PROVINSI NUSA TENGGARA BARAT - Selamat Jalaludin (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2019)
West Lombok Regency is one of the Regencies in the Province of West Nusa Tenggara (NTB) which is a Regional Tourist Destination (DTW) which has a very strategic position as a tourist destination. Tourism development in West Lombok fosters a lot of hope for the community, especially the hope of getting a job outside the agricultural sector. Increasingly crowded tourists who visit are able to open up wider employment opportunities and also have raised hopes that can help increase the income felt by the community. It is well aware that there are several problems that must be of concern to all parties is the lack of community participation in tourism development processes and limitations of each community is different, or even very low in knowledge about tourism development, thus creating the outside community are better able to take advantage in it so that this research will be discussed on How the tourism development and Impact of tourism development on Income communities in the District West Lombok The method used to solve this problem is a qualitative descriptive research method. Based on the research that has been done, it can be concluded that the Development of Tourism in Lombok Barat It started getting better with the availability of berbagai kinds of facilities as well as the impact of tourism development on the income of the people in West Lombok district the shift in the livelihood of the agricultural sector to sector services, such as transportation services, and tour guides, the development of trade and home industry sectors such as shops, stalls, taverns, street vendors, street vendors, and art shops, but the income they get is still far from expectations. it is desirable because they are unable to compete with outside entrepreneurs who have capital, especially traders are more likely to increase the price of merchandise to increase their income but it actually makes tourists shop outside tourist attractions because of lower prices, even if they shop at tourist sites they prefer luxury shops because they are more comfortable so that people's income cannot continue to increase. Keywords: Development, Tourism, Revenue, Society, West Lombok